Crowd-sourced syllabus : a curriculum for resistance - McRae, Leanne (Emerald points., 2020)
Curating the contributions of Twitter users via hashtags, crowd-sourced syllabi respond to evolving crises and critical questions in real time, resulting in living materials for educators and students. This book showcases how these syllabi are filling a gap in educational efficacy by providing access to forgotten, hidden and unpopular resources.